Penyuluhan Cegah Stunting dengan Tolak Pernikahan Dini pada Remaja di SMA PGRI 1 Purwakarta - Yulina Eva Riany; Thariq Final Tamimi; Sinta Naria Suryani; Fadilah Akbar Nurohman; Natasya Aulian Iskandar; Anindya, Amanda; Elsyahra Rieskiza Martha; Nafila Syiffa Cinta Fithria; Ahla Ulya Daradinanti (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Indonesia is one of the countries with the highest rates of early marriage in the world, ranking 37th globally and second in ASEAN after Cambodia. Early marriage is also a concern for policy makers related to marriage, because the risks that can occur are very high. One of the risks is stunting in children who are born. Early marriage and stunting are interrelated because the health and nutrition of the mother before, during, and after pregnancy affect fetal development and the level of stunting risk. This community service activity aims to provide direct counseling to adolescents at one of the high schools in Purwakarta, SMA PGRI 1 Purwakarta. This activity was carried out using a seminar method and structured question and answer in the hall of SMA PGRI 1 Purwakarta with 130 participants. The results of the activity showed that after participating in the counseling activity, there was an increase in knowledge related to stunting and early marriage. This indicates that further programs are needed in other schools so that the dissemination of education can be more widespread.